Communication Skills and Apprehension in Individual Counseling Practices - Violin, Angelia Francitha Tasya; Basuki, Agus (Universitas Negeri Padang, 2024)
This study aims to explore and analyze communication skills and communication apprehension in individual counseling practice, particularly among prospective counselor students. The method used is a literature review, with 216 articles collected and 15 articles selected based on eligibility criteria for in-depth analysis. Findings from this review reveal that high levels of apprehension can hinder students’ ability to interact effectively with counselees and affect the quality of counseling practice. This study also identifies the challenges faced by students in managing their interpersonal communication and assesses the effectiveness of training programs and interventions in improving communication skills and reducing levels of apprehension. The results of this study are expected to provide deeper insights into the importance of communication skills and strategies for overcoming apprehension in the development of counseling competencies.